Encyclopedia of Life Sciences 2019
DOI: 10.1002/9780470015902.a0001056.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Termination ofDNAReplication in Prokaryotes

Abstract: Most bacteria and archaea have circular chromosomes, in which DNA replication begins at a site known as an origin of replication. Double-stranded DNA unwound at the origin creates two replication forks that are engaged by DNA polymerase complexes (replisomes) that advance each fork and proceed in 21 opposite directions away from the origin, copying the original strands. Termination of DNA replication 22 occurs when the two forks meet and fuse, creating two separate double-stranded DNA molecules. In 23 the well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 131 publications
1
4
0
Order By: Relevance
“…We were able to confirm over-replication of the termination area in a strain with a polA2 point mutation ( Midgley-Smith et al, 2018 ). These data are in line with the idea that the fork trap, together with specific proteins such as polymerase I, is involved in bringing DNA replication to a successful conclusion ( Markovitz, 2005 ; Duggin et al, 2008 ; Midgley-Smith et al, 2018 ; Rudolph et al, 2019 ). Similarly, absence of the terminator protein RTP in B. subtilis results in an increased formation of chromosomal dimers, which could arise from a related mechanism ( Lemon et al, 2001 ).…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…We were able to confirm over-replication of the termination area in a strain with a polA2 point mutation ( Midgley-Smith et al, 2018 ). These data are in line with the idea that the fork trap, together with specific proteins such as polymerase I, is involved in bringing DNA replication to a successful conclusion ( Markovitz, 2005 ; Duggin et al, 2008 ; Midgley-Smith et al, 2018 ; Rudolph et al, 2019 ). Similarly, absence of the terminator protein RTP in B. subtilis results in an increased formation of chromosomal dimers, which could arise from a related mechanism ( Lemon et al, 2001 ).…”
Section: Introductionsupporting
confidence: 87%
“…PriA processing will result in the assembly of a new replication fork, the progression of which will not only result in chromosomal over-replication, but also the formation of a doublestranded DNA end (Figure 5v). dsDNA ends will be rapidly processed by the homologous recombination proteins RecBCD and RecA, leading to the formation of a displacement loop (D-loop) (Rudolph et al, 2009(Rudolph et al, , 2013(Rudolph et al, , 2019Dimude et al, 2016;Midgley-Smith et al, 2019). D-loops are yet another substrate for PriA, which means an opportunity for the formation of more replication forks, thus setting up a positive feedback loop of over-replication (Figure 5vi).…”
Section: Making Sense Of the Replication Fork Trap A Role In Preventi...mentioning
confidence: 99%
See 1 more Smart Citation
“…From this point onwards, progression is halted as the forks encounter the 'non-permissive' Tus-Ter complexes. It is here where the two forks thus converge and termination takes place (reviewed in [2,3]). It has been shown that without this tight control there is an accumulation of genomic instability and re-replication [4].…”
Section: Where and When Does Replication Termination Take Place?mentioning
confidence: 99%
“…This is most likely caused by collisions between replication and transcription machineries, as the majority of bacterial genes are encoded on the leading strand and are thus transcribed co-directionally with replication (reviewed in [5]). The fact that multiple rounds of replication can take place at the same time on a bacterial chromosome, with new initiation events taking place before the previous round has completed [3], could also explain why terminating at a specific site is necessary. In bacteria, the sites of replication termination are, therefore, as well defined as the initiation sites.…”
Section: Where and When Does Replication Termination Take Place?mentioning
confidence: 99%